Les representacions de la «sociolingüística catalana» - Querol, Ernest (Caplletra. Revista Internacional de Filologia, 2004)
This article analyses the sociolinguistics elaborated in the Catalan speaking countries, based on a textual corpus. First, different topics are examined; second, the most neglected aspects are indicated (with a theoretical reflection on the paradigm concept and a deep evaluation of Aracil’s work); third, the analysed common loci are compared and their relevance discussed. Finally, the representations of the studied authors are analysed from two different points of view: from a theoretical model based on the Catastrophe Theory and from the sociological paradigm perspective.